QbD Based Development, Characterization and Pharmacokinetic Evaluation of Enzalutamide-Loaded Cyclodextrin Nano Sponges for Enhanced Drug Delivery - Medarametla, Ramya Teja; Radha, Gadela Venkata (Indian Journal of Pharmaceutical Education and Research, 2025)
Aim/Background The aim of this study was to enhance the bioavailability of Enzalutamide by developing cross-linked cyclodextrin nanosponges loaded with the drug (EZL-CDNS). The objective of the work is to thoroughly investigate the impact of different molar ratios of DPC and cyclodextrin on the fundamental properties of EZL-CDNS, such as particle size, entrapment efficiency, and zeta potential. Materials and Methods The Box-Behnken design methodology was employed to systematically investigate the factors affecting the properties of EZL-CDNS. Particle size, entrapment efficiency, and zeta potential were selected as response variables. The experimental design involved varying the molar ratios of DPC and cyclodextrin. The encapsulation of enzalutamide within the nanostructured carriers was confirmed using DSC and FTIR and morphology with SEM. Results The EZL-CDNS exhibited a size distribution ranging from 295 to 471 nm, entrapment efficiency values spanning from 51.7% to 90.7%, and zeta potential values ranging from -15.3 to -28.1 mV. DSC and FTIR analyses confirmed the successful encapsulation of enzalutamide, leading to its transition into an amorphous state. SEM revealed the porous structure of EZL-CDNS. Importantly, in vitro drug release profiles demonstrated a significant improvement compared to pure EZL. Pharmacokinetic Modelling supported a zero-order release pattern, suggesting an enhanced bioavailability profile. EZL-CDNS exhibited a quicker onset of action, higher peak plasma Concentration (Cmax), increased overall drug exposure, and the potential for a sustained release pattern. Conclusion This study successfully developed and characterised EZL-CDNS with different DPC/cyclodextrin molar ratios. Nanostructured carriers had good size distribution, entrapment efficiency, and zeta potential. The increased in vitro drug release profile and pharmacokinetic modelling results suggest higher bioavailability and sustained release of enzalutamide. Further research is needed to confirm these findings and evaluate EZL-CDNS’s clinical uses.
Keywords: Enzalutamide; Cyclodextrin; Nanosponges; Box-Behnken Design; Pharmacokinetics